Pulmonary melioidosis: a review of 70 cases from Pahang, Malaysia - How, Soon Hin; Tee, Hoi Poh; Ab Rahman, Jamalludin; Shah, Anis; Rathor, Mohammad Yousuf (Faculty of Medicine, International Islamic University Malaysia, 2005)
We retrospectively reviewed 70 cases of adult pulmonary melioidosis in Pahang from January 2000 to June 2003. There was a strong association with diabetes mellitus, 82.8% of them were diabetic. Fever was the commonest presentation (96%) followed by cough (75%). 11.8% of patients presented with shock of whom 87.5% died within 24 hours. There was no pathognomonic feature on chest radiograph; but multi-lobar involvement was more common. In our series, B.pseudomallei was most commonly sensitive to cefoperazone-sulbactam (100%), imipenem(100%) and ceftazidime (98.6%). Nearly half (51.4%) of our patients received appropriate empirical antibiotics and the mortality was 71%.